DEVELOPMENT OF A COMPUTER MODULE FOR KINEMATIC AND DYNAMIC ANALYSIS OF IMPORTANT MECHANISMS OF LIGHT INDUSTRIAL MACHINES, PROGRAMS FOR ASSESSING THE TENSION OF TECHNOLOGICAL PROCESSES - SHCHERBAN, Volodymyr; KOLVA, Nikita; EGOROV, Dmitrij; KOLISKO, Oksana; SHCHERBAN, Yuryj (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The development of a computer module for kinematic and dynamic analysis of the lever mechanisms of light industry machines allows determining the parameters that are used in the program to assess the intensity of technological processes of the light and textile industry when determining the change in the relative tension of the thread in the filling zones of the technological equipment. Kinematic and dynamic analysis of flat mechanisms plays a significant role in the design of new mechanisms and modernization of existing ones. The results obtained during these studies can be used to calculate the strength of individual links, their inertial characteristics, optimization of structural parameters of mechanisms, and minimization of consumed energy.A sharp increase in tension leads to a violation of the normal course of the technological process of thread processing. The imperfection of the structural elements of the feed system, thread tensioning devices and thread guides on knitting, textile and sewing machines will not allow thread processing with a sudden increase in input tension. The development of new schemes of the thread feeding system requires an operational assessment of the value of the tension in front of the working zone. To do this, it is effective to use specially developed programs for performing a computational experiment. The tension of the thread increases when moving through the refueling zones of the thread feeding system on the technological equipment. This increase is due to the interaction of the thread with the guides and tension devices. The maximum tension value will be in front of the working area. The development of special computer programs for determining the tension in the working area allows you to determine the necessary technological parameters, make adjustments to both the structure itself and the components of the thread feeding system to obtain the minimum necessary tension in the working area.The objective function in the problem is the minimum necessary tension, which is the minimum sum of the angles covered by the thread of guide surfaces that have a cylindrical, elliptical shape, discrete segments of a straight line. The use of a computer program allows you to determine tensions and changes in relative tension in the filling zones of light and textile industry machines, which allows you to optimize the shape of the thread supply line even at the stage of designing the technological process.The development of application packages of computer programs allows to reduce the time for the design of technological processes in the light and textile industry as much as possible. This is due to the modernization of the thread filling line on the technological equipment, which allows to minimize thread tension in the working area. Minimization of tension is ensured by optimization of the shape of the thread filling line, in which the total angle of coverage of the guides will be minimal. Computer determination of kinematic and dynamic parameters of flat mechanisms allows to determine the parameters used in determining the intensity of technological processes.
Keywords: computer module; kinematic and dynamic analysis; light industry machines; intensity of technological processes